LEGAL POLITICS OF WAQF-REGULATION IN INDONESIA - Aravik, Havis; Yunus, Nur Rohim; Sulastyawati, Dwi (Institut Agama Islam Yasni Bungo, 2019)
The study investigates the government policies in the waqf's regulation in Indonesia and the essence of waqf as an important instrument of economic empowerment in Islam. The study aims to provide solutions to the lack of the benefits of waqf for people's welfare, especially in terms of economic empowerment. It is qualitative research with a normative approach. The research data used is the secondary data from library resources. An analysis of the data is by interpreting the concept. The result of this study shown that waqf has played a major role in citizen empowerment from the time of God's messenger, Muhamad peace be upon him until now, even the benefits of a waqf can still be felt up to today. Keywords: waqf, political law, legislation.